Critical velocity determined by a non-exhaustive method in menopausal women - Rossi, F. E. [UNESP]; Kalva-Filho, C. A.; Gavassa de Araújo, R.; Gerosa Neto, J. [UNESP]; Campos, E. Z. [UNESP]; Pastre, C. M. [UNESP]; Papoti, M.; Freitas Junior, I. F. [UNESP] (Elsevier, 2015)
The aim of the present study was to test the reproducibility of critical velocity determined in a non-exhaustive method (CVNE) and its relationship with the maximal lactate steady state (MLSS) in menopausal women. Methods: Nine women (aged 59.8 [4.6] years) were subjected to two efforts, of the same intensity, in each session, lasting 180s and separated by an interval of 90s. The blood lactate ([Lac]) and heart rate (HR) differences (Delta; δ) between the first and second sessions were determined. The session intensities corresponded to 4, 5 and 6km.h-1. The CVNE was assumed to be the Y-intercept between the δs and the intensities. Results: The CVNE, determined through the [Lac] (test=5.4±0.7; retest=5.0±0.6) and HR (test=4.8±0.4; retest=4.9±0.5), was not significantly different between the conditions. However, no correlation was observed between test and retest situations for the CVNE determined through the [Lac] (r=0.29) or the HR (r=-0.16). Furthermore, CVNE determined through both variables significantly underestimated and was not correlated with MLSS. Conclusion: Thus, it can be concluded that CVNE does not have high reproducibility and cannot be used to estimate the MLSS in postmenopausal women.
Keywords: Critical velocity; Maximal lactate steady state; Menopausal women; Non-exhaustive test